Review of socio-residential vulnerability identification methodologies. Application to the cities of Bilbao and Barcelona - Pilar García Almirall; Còssima Cornadó; Gonzalo Piasek; Sara Vima Grau (Vitruvio: International Journal of Architectural Technology and Sustainability)
This article presents the most widely used methodologies to measure, analyse and assess the state of the building stock and the life conditions of people living in vulnerable neighbourhoods, in an attempt to identify limitations and opportunities within the design of more suitable instruments that will allow us to identify residential communities in a vulnerable situation, residential exclusion or at difficulty to access rehabilitation subsidies or allowances. The methodology adopted is based on the obtention of a first vulnerability index constructed from quantitative data that allows us to focus on the most vulnerable areas of the cities under study. Later, it is complemented with qualitative analysis, interviews to technical officers, entities’ representatives, and site visits and observations. The main obtained results consist of different methodological approaches and analytic and geospatial measurements of the residential vulnerability in the cities of Barcelona and Bilbao: from quantitative large-scale multicriterial analysis, geospatial analysis on specific aspects, to small-scale qualitative study cases, fieldwork and interviews to different actors. In conclusion, by applying those different methodologies in the same specific areas, we were able to determine how data disaggregation and specificity in relation to urban and building form and location provide relevant differential results that help to qualify certain patterns that can be detected but not explained by quantitative larger-scale integrative analysis. Besides, the qualitative information provided by key local agents of different networks was crucial to explain and understand the nature of geographical and time-changing patterns of residential vulnerability.